Laying the foundations: A bibliometric analysis of L2 vocabulary research in 1982-1986 - Meara, Paul (LingBaW. Linguistics Beyond and Within, 2018)
This paper uses a co-citation analysis to examine the research on L2 vocabulary acquisition that was published in 1986. This year seems to mark a serious consolidation of L2 vocabulary research, with the main themes of future research appearing. The paper also reports a larger analysis of all the work that appeared in a five-year window from 1982-1986. This analysis clearly shows the beginnings of a recognisable research focus on L2 vocabulary acquisition, though this work is influenced by some surprising sources, who do not figure in more recent work in the field.